1995
DOI: 10.1002/nau.1930140305
|View full text |Cite
|
Sign up to set email alerts
|

Reduced variance of latencies in pudendal evoked potentials after normalization for body height

Abstract: The value of the Somatosensory Evoked Potentials (SEP) in the assessment and detection of neurological disorders could be considerably enhanced if the normative standards of (SEP) characteristic parameters were normalized taking into account all other systematic sources of variance. The present study examines the influence of body height on the peak and interpeak latencies of the pudendal somatosensory evoked potentials. We examined the peak latency (L1) of the evoked potential recorded at the L1 vertebra and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…However, there is still controversy about the exact topographical distribution and density of the urethral sensory innervation in humans and minimal P1 latencies were clearly longer than normal pudendal SEP latencies for clitoral, penile, or perineal stimulation sites. 21 Tallying with this some subjects demonstrated early potentials for mUR and dUR that could be attributed to afferent pudendal activation. Interestingly, SEPs from mUR were more difficult to assess and demonstrated a higher N1 latency variability compared to the other LUT locations.…”
Section: Figurementioning
confidence: 62%
See 1 more Smart Citation
“…However, there is still controversy about the exact topographical distribution and density of the urethral sensory innervation in humans and minimal P1 latencies were clearly longer than normal pudendal SEP latencies for clitoral, penile, or perineal stimulation sites. 21 Tallying with this some subjects demonstrated early potentials for mUR and dUR that could be attributed to afferent pudendal activation. Interestingly, SEPs from mUR were more difficult to assess and demonstrated a higher N1 latency variability compared to the other LUT locations.…”
Section: Figurementioning
confidence: 62%
“…Faster conducting fibers belonging to the pudendal nerve that contribute to the afferent innervation of the distal parts of the urethra may contribute to this finding. However, there is still controversy about the exact topographical distribution and density of the urethral sensory innervation in humans and minimal P1 latencies were clearly longer than normal pudendal SEP latencies for clitoral, penile, or perineal stimulation sites . Tallying with this some subjects demonstrated early potentials for mUR and dUR that could be attributed to afferent pudendal activation.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also confirmed the previously reported absence of correlation between the subject's height and latency of the sacral reflex on single electrical stimulation. 27 The absence of correlation between anatomic length of the sacral reflex arc and reflex latency underlines the relatively more important central conduction delay within the conus medullaris in comparison to conduction along afferent and efferent nerve pathways. No correlation of age with latency or any other measured parameter was also found.…”
Section: Discussionmentioning
confidence: 99%
“…Latencies of the peak of the first positive deflection (so-called P1 wave) are given in Table 3. Latencies for three of those subjects (starred) were longer (> mean +3 SD) than expected from a control, neurologically normal population allowing for the height of subjects [18]. Table 3 changes were also observed in 5 subjects who lacked a pSSEP.…”
Section: Afferent Pathwaymentioning
confidence: 67%